Mast cell derived carboxypeptidase A3 is decreased among patients with advanced coronary artery disease - Lewicki, Łukasz (Cardiol J, 2020)
BACKGROUND: Coronary artery disease (CAD) affects milions of people and can result in myocardial infarction (MI). Previously, mast cells (MC) have been extensively investigated in the context of hypersensitivity, however as regulators of the local inflammatory response they can potentially contribute to CAD and/or its progression. The aim of the study was to assess if serum concentration of MC proteases: carboxypeptidase A3, cathepsin G and chymase 1 is associated with the extension of CAD and MI. METHODS: The 44 patients with angiographically confirmed CAD (23 subjects with non-ST-segment elevation MI [NSTEMI] and 21 with stable CAD) were analyzed. Clinical data were obtained as well serum concentrations of carboxypeptidase A3, cathepsin G and chymase 1 were also measured. RESULTS: Patients with single vessel CAD had higher serum concentration of carboxypeptidase than those with more advanced CAD (3838.6 ± 1083.1 pg/mL vs. 2715.6 ± 442.5 pg/mL; p = 0.02). There were no significant differences in levels of any protease between patients with stable CAD and those with NSTEMI. Patients with hypertension had ≈2-fold lower serum levels of cathepsin G than normotensive individuals (4.6 ± 0.9 pg/mL vs. 9.4 ± 5.8 pg/mL; p = 0.001). Cathepsin G levels were also decreased in sera of the current smokers as compared with non-smokers (3.1 ± 1.2 ng/mL vs. 5.8 ± 1.2 ng/mL, p = 0.02). CONCLUSIONS: Decreased serum level of carboxypeptidase is a hallmark of more advanced CAD. Lower serum levels of carboxypeptidase A3 and catepsin G are associated with risk factors of blood vessel damage suggesting a protective role of these enzymes in CAD.